POTENSI DAN PROSPEK PENGEMBANGAN PANGAN TRADISIONAL DI KECAMATAN MATTIRO BULU KABUPATEN PINRANG - Hamka Hamka; Akhsan Akhsan; Dayu Suhardi (Cateris Paribus Journal, 2026)
The potential and prospects for the development of traditional foods represent a strategic effort to boost the local economy based on local resources. This study aims to analyze the potential and prospects for the development of traditional foods in Mattiro Bulu Subdistrict, Pinrang Regency. This study employs a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. The research informants consisted of 10 home industry entrepreneurs selected using purposive sampling. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Mattiro Bulu Subdistrict possesses abundant local resources, particularly in the agricultural sector, such as rice, corn, bananas, and tubers. However, the utilization of this potential remains suboptimal due to limitations in human resources, a lack of product innovation, and low adoption of digital technology. The strategies employed by business operators remain rudimentary, including setting affordable prices, limited product innovation, and conventional promotion. The research findings also reveal a gap between high local potential and low business management capacity, necessitating support through training, mentoring, and the digitalization of SMEs to enhance the competitiveness of traditional food products.